Impact of Global Geopolitical Tension and Economic Uncertainty on Economic Growth in 3 Countries OIC - Firliana Rizki Ramadhina; Inda Fresti Puspitasari (Universitas Muhammadiyah Surakarta, 2025)
Purpose: The study aims to examine the impact of geopolitical tension and global economic uncertainty on economic growth. The dependent variable in this study is GDP Growth, while the independent variables in this study are Geopolitical Risk Index (GPR), World Uncertainty Index (WUI), Oil Prices, and Gold Prices).Methodology: This study uses a quantitative panel data analysis method in three OIC countries (Saudi Arabia, Indonesia, and Malaysia) for the period 2020 M01-2024 M12. Results: The Best model in this study is Fixed Effect Model (FEM). The results show that World Uncertainty Index (WUI) and Oil Prices have a positive and significant effect on economic growth, while Gold Prices have a negative and significant effect. Meanwhile, GPR has no significant effect on economic growth. Applications/Originality/Value: Results of this study can be a suggestion for government to maintain economic growth with implication expansionary fiscal policies such as increasing Infrastructure spending, creating labor intensive programs, and providing energy subsidies.